2015
DOI: 10.1186/s13028-015-0097-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the animal species contents of popular wet pet foods

Abstract: BackgroundThe use of the generic term “meat and animal derivatives” in declared ingredient lists of pet foods in the European Union is virtually universal. In the wake of the 2013 “horse meat scandal” in the human food chain, we examined the presence and authenticity of animal sources (cow, chicken, pig and horse) of proteins in a range of popular wet pet foods in the United Kingdom.FindingsSeventeen leading dog and cat foods were sampled for the relative presence of DNA from each of the four animal species by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
0
18
0
Order By: Relevance
“…This may also be due to the absence of mammalian DNA or to DNA degradation secondary to the canning process. Other studies have reported detection of mammalian DNA in canned canine and feline diets using methods such as reverse transcription PCR (Pegels et al., ; Maine et al., ; Okuma and Hellberg, ) or PCR‐restriction fragment length polymorphism (Hsieh et al., ). Therefore, utilization of other detection methods may have yielded different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also be due to the absence of mammalian DNA or to DNA degradation secondary to the canning process. Other studies have reported detection of mammalian DNA in canned canine and feline diets using methods such as reverse transcription PCR (Pegels et al., ; Maine et al., ; Okuma and Hellberg, ) or PCR‐restriction fragment length polymorphism (Hsieh et al., ). Therefore, utilization of other detection methods may have yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the presence of undeclared ingredients in foods, supplements and treats for pets by detection of microscopic bone fragments, protein by enzyme‐linked immunosorbent assay (ELISA) and deoxyribonucleic acid (DNA) by polymerase chain reaction (PCR), reverse transcription PCR, multiplex PCR and PCR‐restriction fragment length polymorphism (Dalmasso et al., ; Myers et al., ; Wang et al., ; Raditic et al., ; Ricci et al., ; Parr and Remillard, ; Pegels et al., ; Hsieh et al., ; Maine et al., ; Okuma and Hellberg, ). While only the results of samples collected at one time point have been reported, these findings have prompted questions regarding quality control in diet formulation and manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not easy to identify all of the protein sources with which the dog has come into contact 4, 7. Moreover, some commercial petfood diets, even those specified for an elimination dietary trial, contain animal proteins other than those declared in the ingredient list 8, 9. Vegetable proteins can be found in traces in pet food, but are less likely to cause allergic reactions 7.…”
Section: Introductionmentioning
confidence: 99%
“…(Milch et al 1957) and can remain fixed for extended periods in treated animals even respecting withdrawal times (Odore et al 2015). Moreover, pet food production relies on meal (mainly poultry) by-products (Maine et al 2015) in which an important percentage of bone meal (20-30%) is present. This mix very often drags behind oxytetracycline residues that are present in commercially available diets (canned, semi-moist and dry) and can accumulate within the pet's body.…”
Section: Discussionmentioning
confidence: 99%